2014
DOI: 10.1021/ac500567g
|View full text |Cite
|
Sign up to set email alerts
|

Polyion Selective Polymeric Membrane-Based Pulstrode as a Detector in Flow-Injection Analysis

Abstract: A method for the detection of polyions using fully reversible polyion selective polymeric membrane type pulstrodes as detectors in a flow-injection analysis (FIA) system is examined. The detection electrode consists of a plasticized polymeric membrane doped with 10 wt % of tridodecylmethylammonium-dinonylnaphthalene sulfonate (TDMA/DNNS) ion-exchanger salt. The pulse sequence used involves a short (1 s) galvanostatic pulse, an open-circuit pulse (0.5 s) during which the EMF of the cell is measured, and a longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…While all sensors used in the these studies were discarded after a single use, sensors can be regenerated by soaking in 3M NaCl for reuse with a minimal decrease in sensitivity, as has also been demonstrated for other polyanions [39,42]. A more promising approach would be to use a fully reversible, pulsed chronopotentiometric polymer membrane electrode, similar to that first described for the linear polycation protamine [51,52], and later developed for linear polyanions, such as heparin and pentosan polysulfate [53,54]. Based on the results presented herein, fucoidan detection via pulsed chronopotentiometry should be readily attainable.…”
Section: Non-equilibrium Fucoidan Detectionmentioning
confidence: 99%
“…While all sensors used in the these studies were discarded after a single use, sensors can be regenerated by soaking in 3M NaCl for reuse with a minimal decrease in sensitivity, as has also been demonstrated for other polyanions [39,42]. A more promising approach would be to use a fully reversible, pulsed chronopotentiometric polymer membrane electrode, similar to that first described for the linear polycation protamine [51,52], and later developed for linear polyanions, such as heparin and pentosan polysulfate [53,54]. Based on the results presented herein, fucoidan detection via pulsed chronopotentiometry should be readily attainable.…”
Section: Non-equilibrium Fucoidan Detectionmentioning
confidence: 99%
“…It is well known that traditional methods for polyion detection can be challenging, as these molecules have high molecular weights and do not absorb light at wavelengths >260 nm. 14 In addition, traditional electrochemical methods of detection are often not suitable since PQs do not possess redox active domains for analysis via conventional cyclic voltammetry 14,15 or related amperometric/voltammetric techniques. To circumvent this challenge, it was recently demonstrated that polyion-sensitive ion-selective electrodes (ISEs) can be used to quantify and characterize PQ species in solution.…”
Section: Introductionmentioning
confidence: 99%
“…By using a modified lipophilic salt and improved electrochemical pulse sequence, a pulstrode for reversible detection of polyanions was recently proposed by our group 10. We further applied, for the first time, this new polyion pulstrode technology as a detector in conventional flow‐injection analysis (FIA) systems 11. Multiple polycation and polyanion samples can be analyzed sequentially using such a FIA system with the potentiometric membrane electrode detector.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple polycation and polyanion samples can be analyzed sequentially using such a FIA system with the potentiometric membrane electrode detector. Further, concentrations of both polycations and polyanions can be monitored with the same device simply by reversing the polarity of the current used to polarize the lipophilic ion‐exchanger species within the polymeric membrane 11. In related work, Qin’s group proposed a reversible and sensitive polyion sensing strategy based on controlled release of the polyion from a polymeric membrane 1214, and further applied this technique in flow‐injection analysis of aptamers and heparin 15, 16.…”
Section: Introductionmentioning
confidence: 99%